Smart grids as cyber physical systems : smart grids paving the way to smart cities - Swathika, O.V. Gnana; Karthikeyan, K.; Padmanaban, Sanjeevikumar (Hoboken : Wiley, 2024)
Smart Grids as Cyber Physical Systems, a new two-volume set from Wiley-Scrivener, provides a comprehensive overview of the fundamental security of supervisory control and data acquisition (SCADA) systems, offering clarity on specific operating and security issues that may arise that deteriorate the overall operation and efficiency of smart grid systems. It also provides techniques to monitor and protect systems, as well as aids for designing a threat-free system. This title discusses how artificial intelligence (AI) may be extensively deployed in the prediction of energy generation, electric grid-related line loss prediction, load forecasting, and for predicting equipment failure prevention. It also discusses power generation systems, building service systems, and explores advances in machine learning, artificial neural networks, fuzzy logic, genetic algorithms, and hybrid mechanisms. Additionally, we will explore research contribution of experts in CPS infrastructure systems, incorporating sustainability by embedding computing and communication in day-to-day smart grid applications. This book will be of immense use to practitioners in industries focusing on adaptive configuration and optimization in smart grid systems. Through case studies, it offers a rigorous introduction to the theoretical foundations, techniques, and practical solutions CPS offers. Building CPS with effective communication, control, intelligence, and security is discussed from societal and research perspectives and a forum for researchers and practitioners to exchange ideas and achieve progress in CPS is provided by highlighting applications, advances, and research challenges. This book offers a comprehensive look at ICS cyber threats, attacks, metrics, risk, situational awareness, intrusion detection, and security testing, providing a valuable reference set for current system owners who wish to configure and operate their ICSs securely.
Keywords: Smart Grid; Systems Engineering & Management; Batteries & Fuel Cells; Power; Electricity; Smart Economy; Smart Governance; Smart Environment; Smart Mobility; Smart Population; Digital Data; Infrastructure; Software; Urban Transport; Network; User Application; Development Process; Intelligent System; Electronic books